Kepribadian Ihsan dan Faktor yang mempengaruhi Kualitas Laporan Keuangan Pemerintah Daerah - Ariani, Nadia Elsa; Arif Afendi (Indonesian Journal of Applied Accounting and Finance, 2024)
Financial statements are made as a form of accountability for regional financial management to the general public and also the parties concerned. The preparation of these financial statements is a form of accountability, namely as reporting in realizing organizational goals. Good financial statements certainly meet the normative requirements of financial statement quality. The financial statements of the Local Government of Jepara Regency have received an unqualified opinion eleven times in a row. However, the opinion obtained still receives additional notes, in the sense that this fair opinion without exclusion is accompanied by a special explanatory note as material for improvement in the financial statements of the Regional Government in the future. This study was conducted to examine the influence of ihsan personality, work environment, and partial internal control on the quality of financial statements of the Local Government of Jepara Regency, Central Java.  The population in this study is 65 institutions in Government Organizations that perform accounting and finance functions on. The samples used are 22 Sections which include 17 Government institutions and 5 agencies. The method in this study uses quantitative methods with descriptive analysis techniques and multiple linear regression analysis as well as sampling with non-probability sampling techniques with purposive sampling. The results of this study explain that ihsan's personality has a positive effect on the quality of financial statements. Furthermore, the work environment does not have a positive effect on the quality of financial statements, and the last internal control is obtained to have a positive effect on the quality of financial statements at the Jepara Local Government Organization. This research contribution provides recommendations to local governments to improve transparency, accountability, and integrity in the preparation of financial statements. In addition, this study can also provide new insights for researchers and practitioners in the field of government accounting to pay more attention to aspects of individual personality in an effort to improve the quality of financial statements